2022
DOI: 10.1097/mnm.0000000000001573
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of conventional and volumetric PET parameters with and without partial volume correction in the assessment of head and neck squamous cell carcinoma

Abstract: BackgroundThe optimal quantification of PET in assessment of head and neck squamous cell carcinoma (HNSCC) is still under development. The effect of partial volume correction (PVC) on the evaluation of survival in the HNSCC patients has not been investigated yet.Methodology Pretreatment 18 F-FDG-PET/CT scans of a selected group of 57 patients with advanced stage HNSCC were collected. Conventional (SUVmean and SUVmax) and volumetric [total lesion glycolysis (TLG) and metabolic tumor volume (MTV)] PET metrics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…MTV and TLG have been reported to be useful for predicting recurrence, metastasis, and prognosis of head and neck cancer, including oral cancer, and in various other areas of cancer. [5][6][7][8][35][36][37][38] Suzuki-Shibata et al, [39] Lim et al, [40] and Kim et al, [41] reported the usefulness of metabolic volume-based parameters for predicting the efficacy of chemotherapy and molecular-targeted drug therapy. Recently, metabolic volume-based parameters have been considered for local diagnostic applications with regional specificity, such as the relationship between glucose metabolism and epithelial-mesenchymal interactions, [42] the relationship between differentiation and clinical progression.…”
Section: Discussionmentioning
confidence: 99%
“…MTV and TLG have been reported to be useful for predicting recurrence, metastasis, and prognosis of head and neck cancer, including oral cancer, and in various other areas of cancer. [5][6][7][8][35][36][37][38] Suzuki-Shibata et al, [39] Lim et al, [40] and Kim et al, [41] reported the usefulness of metabolic volume-based parameters for predicting the efficacy of chemotherapy and molecular-targeted drug therapy. Recently, metabolic volume-based parameters have been considered for local diagnostic applications with regional specificity, such as the relationship between glucose metabolism and epithelial-mesenchymal interactions, [42] the relationship between differentiation and clinical progression.…”
Section: Discussionmentioning
confidence: 99%